3D Printing Hip Prostheses Offer Accurate Reconstruction, Stable Fixation, and Functional Recovery for Revision Total Hip Arthroplasty with Complex Acetabular Bone Defect. (November 2020) - Hao, Yongqiang; Wang, Lei; Jiang, Wenbo; Wu, Wen; Ai, Songtao; Shen, Lu; Zhao, Shuang; Dai, Kerong
Abstract: Complicated and large acetabular bone defects present the main challenges and difficulty in the revision of total hip arthroplasty (THA). This study aimed to explore the advantages of three-dimensional (3D) printing technology in the reconstruction of such acetabular bone defects. We retrospectively analyzed the prognosis of four severe bone defects around the acetabulum in three patients who were treated using 3D printing technology. Reconstruction of bone defect by conventional methods was difficult in these patients. In this endeavor, we used radiographic methods, related computer software such as Materialise's interactive medical image control system and Siemens NX software, and actual surgical experience to estimate defect volume, prosthesis stability, and installation accuracy, respectively. Moreover, a Harris hip score was obtained to evaluate limb function. It was found that bone defects could be adequately reconstructed using a 3D printing prosthesis, and its stability was reliable. The Harris hip score indicated a very good functional recovery in all three patients. In conclusion, 3D printing technology had a good therapeutic effect on both complex and large bone defects in the revision of THA. It was able to achieve good curative effects in patients with large bone defects.